The safety of pneumococcal vaccines at the time of sequential schedule: data from surveillance of adverse events following 13-valent conjugated pneumococcal and 23-valent polysaccharidic pneumococcal vaccines in newborns and the elderly, in Puglia (Italy) - Di Lorenzo, A.; Martinelli, A.; Bianchi, F. P.; Scazzi, F. L.; Diella, G.; Tafuri, S.; Stefanizzi, P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Nowadays, two types of anti-pneumococcal vaccine are available: pneumococcal 13-valent conjugate vaccine (PCV13), first licensed in the United States (US) in 2013, and pneumococcal 23-valent polysaccaridic vaccine (PPSV23), first licensed in the US in 1999. These vaccines are recommended in Italy for the immunization of newborns and of the elderly, using a combined sequential schedule for the latter. This report aims to describe the PCV13- and PPSV23-related AEFIs notified in Puglia in 2013-2020, in order to design these products’ safety profile in a real-life scenario, three years after the official recommendation about the sequential schedule for people over 60 years of age. Methods. This is a retrospective observational study. Data were gathered from the list of AEFIs notified following PCV13 and PPSV23 administration in Puglia in 2013-2020. The number of administered vaccine doses was obtained from the regional immunization database. AEFIs were classified according to WHO’s algorithm, and causality assessment was carried out in case of serious AEFIs.Results. From January 2013 to December 2020, 764,183 doses of PCV13 and 40,382 doses of PPSV23 were administered in Puglia. In the same period, 71 PCV13 AEFIs (Reporting Rate: 9.29 x100,000 doses) and 5 PPSV23 AEFIs (Reporting Rate: 12.4 x100,000 doses) were reported.The overall male/female ratio in AEFIs was 0.85. The majority of AEFIs occurred in subjects aged less than 2 (64/76, 84.2%), while 10 out of 76 (13.2%) occurred in patients aged 60 or older. 22 AEFIs were classified as serious and for 12 (54.5%) causality assessment showed a consistent relationship with immunization. The most commonly reported symptoms were fever (Reporting Rate: 4.72 x100,000 doses) and neurological symptoms (Reporting Rate: 3.23 x100,000 doses). Only one death was notified, classified as non-vaccinerelated.Conclusions. The benefit of pneumococcal vaccination appears to be greater than the risk of AEFIs for both PCV13 and PPSV23. In fact, AEFIs occur in less than 0.1‰ of patients and the majority of AEFIs are mild and self-limiting.